Vericiguat attenuates cyclosporine A-induced nephropathy by targeting the NF-κB/TGF-β1 axis: an integrated network pharmacology, Mendelian randomization, and experimental study - Liu, XuanKe; Tang, MengJie; Lu, JiaYing; Kong, YiJing; Shen, WenXuan; Zhang, ChunJiang; Yang, XiaoPing (Frontiers in Immunology, 2026)
BackgroundCyclosporine A (CsA)-induced nephrotoxicity is a significant cause of chronic kidney disease (CKD), primarily driven by aberrant activation of the NF-κB and TGF-β1 signaling axes. Vericiguat, a soluble guanylate cyclase (sGC) stimulator, has established cardioprotective effects, but its potential renoprotective role and underlying mechanisms in CsA-induced CKD remain unexplored.MethodsAn integrative approach was employed. Network pharmacology identified common targets between vericiguat and CKD. Mendelian randomization (MR) analysis assessed the causal relationship between drug target genes and CKD risk. The therapeutic effects and mechanisms of vericiguat were subsequently validated in vivo using a CsA-induced mouse model and in vitro in human renal tubular epithelial (HK-2) cells.ResultsIntegrated computational analyses pinpointed the NF-κB/TGF-β1 axis as a core target of vericiguat. In mice, vericiguat treatment dose-dependently ameliorated CsA-induced renal dysfunction, proteinuria, renal inflammation, oxidative stress, and fibrosis. In HK-2 cells, vericiguat suppressed CsA-triggered inflammatory cytokine secretion, fibrotic marker expression, and reactive oxygen species production. Mechanistically, vericiguat inhibited the phosphorylation of the IKKβ/IκBα/NF-κB p65 pathway and the activation of TGF-β1/Smad signaling, thereby disrupting the inflammation-fibrosis vicious cycle. Genetic manipulation confirmed p65 as a crucial nodal point in this regulatory network.ConclusionThis study demonstrates that vericiguat exerts renoprotective, anti-inflammatory, and anti-fibrotic effects in CsA-induced CKD by modulating the NF-κB/TGF-β1 axis. These findings provide a novel scientific rationale for drug repurposing of vericiguat and highlight its potential therapeutic value for CKD.